Pembuatan dan Pengarahan Media Mewarnai Gambar Bagi Anak Usia 1-8 th di BTN Kasumberang Kabupaten Gowa - Faidhul Inayah; Dwi Wahyuni Hamka; Evi Ristiana; Rahmat Kurniawan; Muhammad Syafruddin Akmal (Program Studi Manajemen FEB UNM, 2023)
The Implementation of the Drawing-Coloring Media Making and Guiding Activities which were carried out at BTN Kasumang, Gowa Regency, were attended by 15 children aged 1-8 years. This activity consists of two stages, namely the planning stage and the implementation stage. This activity is able to arouse children's interest in carrying out activities that have learning content. In addition, they must also be able to develop interesting and fun learning strategies. The objectives of this activity include: (a) presenting a form of creative activity. (b) providing image media designs that can be colored as instruments for learning activities (c) creating and directing media images to improve the motor skills and creativity of children aged 1-8 years at BTN Kasumang, Gowa Regency